2020
DOI: 10.33899/ijvs.2020.126135.1242
|View full text |Cite
|
Sign up to set email alerts
|

The genotype of Entamoeba histolytica in bloody diarrhea samples of humans, cows and sheep

Abstract: The present study was carried out to detect the genotype of E. histolytica that found in human fecal specimens and animals feces with Haemorrgic diarrhea by amplifying the SREHP gene, using RT-PCR technique, Cyber green dye and by fusion curve analysis. The study also included molecular detection of amoebic parasite species using Nested-PCR technology. The study recorded presence of parasites E. histolytica; E. dispar; E. bovis with total infection rates 82.9, 26.8, 4.9%, respectively. The study revealed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The veterinarians who completed postmortem examination also disregarded the protozoan infections when the infection led to partial condemnation of the carcass due to the presence of liver abscesses from Entamoeba species infection which it has the ability to devour red blood cells by Erythrophagocytosis through the process of analyzing its plasma membrane (29,30). In the current study, the frequency of protozoan infections was lower than the normal range reported in other studies.…”
Section: Discussionmentioning
confidence: 53%
“…The veterinarians who completed postmortem examination also disregarded the protozoan infections when the infection led to partial condemnation of the carcass due to the presence of liver abscesses from Entamoeba species infection which it has the ability to devour red blood cells by Erythrophagocytosis through the process of analyzing its plasma membrane (29,30). In the current study, the frequency of protozoan infections was lower than the normal range reported in other studies.…”
Section: Discussionmentioning
confidence: 53%
“…Although continuous IBV cases are detectable in most of the broiler farms in Duhok province, there have been no reports on circulating IBV strains or genotyping of this virus in the area. RT-PCR and Nested PCR have been widely used in this concern due to their efficiency in the identification and genotyping of the isolated IBV and other infectious agents in the broiler and other animals (16)(17)(18)(19). Therefore, this study was aimed to genotype the collected positive samples to IBV in the broiler fields in Duhok province, in Iraq.…”
Section: Discussionmentioning
confidence: 99%